Design, Synthesis and Biological Evaluation of Some Novel Hexahydroquinoline-3-carbonitriles as Anticancer and Antimicrobial Agents - M. Faidallah*, Hassan; A. Saqer, Alaa; A. Alamry, Khalid.; A. Khan, Khalid; A.M. Zayed, Mohie; A. Khan, Salman (Asian Journal of Chemistry, 2014)
The synthesis of ten novel 3-cyano-8-methyl-2-oxo-1,4-disubstituted-1,2,5,6,7,8-hexahydro-quinolines supported with benzensulfonyl and phenylthiocarbamoyl pharmacophores that are known to contribute to potential chemotherapeutic effects is described. They were evaluated in vitro for their antimicrobial activity against eight different microorganisms and for their cytotoxic effects against three different human tumor cell lines. The results revealed that nine compounds displayed variable inhibitory effects on the growth of the tested Gram-positive and Gram-negative bacteria with special pronounced activity against S. aureus and E. coli bacterial strains, in addition to a moderate antifungal activity against C. albicans. On the other hand, six compounds were able show remarkable cytotoxic efficiency against human colon carcinoma HT29, hepatocellular carcinoma Hep-G2 and Caucasian breast adenocarcinoma MCF7 cell lines. Collectively, the results would suggest that compounds 15 and 16 could be considered as possible dual antimicrobial-anticancer agents.